Blendas de PHB e seus copolímeros: miscibilidade e compatibilidade Blends of PHB and its copolymers: miscibility and compatibility - Antonio Carlos Quental (Química Nova, 2010)
Poly(hydroxybutyrate) and its copolymers are linear polyesters behaving as conventional thermoplastic materials. However, they are totally biodegradable and produced by a wide variety of bacteria from renewable sources. Some properties and high production cost are still preventing future applications. In an attempt to improve the properties and to reduce cost blending PHB with others polymeric materials is one of the most efficient method. In this paper, miscibility, compatibility, morphological and mechanical aspects of PHB blends will be reviewed. An extensive revision over twenty last years was realized about works of blends based on PHB and its copolymers.